BANJIR BANDANG DI ALASMALANG BANYUWANGI DAN ALTERNATIF PENANGANANNYA (Flash flood at Alasmalang Banyuwangi and alternatives for its completion) - Rokhmat Hidayat; Jati Iswardoyo (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2019)
ABSTRACTFlash floods frequently occur in Indonesia. Flash flood can be caused by natural and human factors. This paper discusses the causes and mitigation of flash flood using a case study in Banyuwangi. On June 22th 2018, flash floods occurred in the residential areas of Garit, Karang Asem, and Bangunrejo Hamlets. Flash floods were triggered by heavy rainfall the day before, which reached 90 mm/day. The three hamlets are located in Alasmalang Village, Singojuruh Subdistrict, Banyuwangi District. The study began with a field survey, analysis of the damage, and the causes of a flash flood, and its alternative treatments. The suspected source of the material was the landslide material, approximately two million cubic meters from the Pendil Mountain. Some of the material were carried away by the river flooding caused flash floods in the three hamlets. The small width of the bridge was not able to be passed by trees and other flash flood material, so water overflowed the roads and houses. Based on the results of the study, it is recommended for disaster mitigation in the form of structural and non-structural actions. Structural measure in the form of bridge elevation and construction of sediment retaining weirs, while non-structural actions are in the form of an early warning system and dissemination of flash flood hazards.Keywords: Flash flood; landslide; structural treatments; non-structural treatments ABSTRAKBanjir bandang sering terjadi di Indonesia. Banjir bandang dapat disebabkan oleh faktor alami maupun manusia. Makalah ini membahas tentang penyebab dan mitigasi banjir bandang dengan studi kasus di Banyuwangi. Pada 22 Juni 2018 banjir bandang melanda kawasan permukiman di Dusun Garit, Karang Asem, dan Bangunrejo. Banjir bandang dipicu hujan lebat sehari sebelumnya mencapai 90 mm/ hari. Tiga dusun itu berada di Desa Alasmalang, Kecamatan Singojuruh, Banyuwangi. Penelitian diawali dengan survei lapangan, analisis kondisi kerusakan akibat banjir bandang, penyebab banjir bandang, serta alternatif penanganannya. Sumber material diduga berupa material longsor sekitar dua juta meter kubik dari Gunung Pendil. Sebagian material ini terbawa banjir sungai sehingga menyebabkan banjir bandang di tiga dusun tersebut. Kondisi lebar jembatan yang kecil tidak mampu dilalui oleh pepohonan dan material banjir lain, sehingga banjir meluap menggenangi jalan dan rumah warga. Berdasarkan hasil kajian maka direkomendasikan untuk penanggulangan dan mitigasi bencana berupa tindakan struktural dan tindakan non struktural. Tindakan struktural berupa peninggian jembatan dan pembangunan bending penahan sedimen, sedangkan tindakan nonstruktural berupa sistem peringatan dini dan sosialisasi bahaya banjir bandang.Kata kunci: Banjir Bandang; longsor; penanganan struktural; penanganan non-struktural